Predicting Global Halal Travel Industry Market Share - Fathi, Muhammad; Shandyka, Muhammad Taqy; Putra, Gian Adit (SMART Insight, 2024)
The halal travel industry is one of the fastest-growing sectors in the global Islamic economic ecosystem. As the number of the world's Muslim population increases, the need for tourism services in accordance with sharia principles is also increasing. This study aims to predict the market share (market size) of the global halal travel industry using historical data for the period 2012–2017. Data was obtained from the Global Islamic Economics Report (GIER) 2018 published by Thomson Reuters. The analysis methods used include Trend Analysis, Multiplicative Decomposition, and Exponential Smoothing with Trend with the help of POM-QM software version 3. The results of the study show that in general, the market share of the global halal travel industry has experienced a significant increasing trend. Based on the forecasting accuracy indicator measured through the Mean Absolute Percentage Error (MAPE) value, the Trend Analysis and Multiplicative Decomposition methods show a relatively better level of accuracy than the Exponential Smoothing with Trend method. These findings are expected to be a reference for policymakers and industry players in formulating strategies for the development of the halal travel industry at the global level.